2023
DOI: 10.3389/fneur.2023.1244696
|View full text |Cite
|
Sign up to set email alerts
|

Functional brain activity in patients with amnestic mild cognitive impairment: an rs-fMRI study

Jinhuan Yue,
Sheng-wang Han,
Xiao Liu
et al.

Abstract: BackgroundAmnestic mild cognitive impairment (aMCI) is an early stage of Alzheimer’s disease (AD). Regional homogeneity (ReHo) and amplitude of low-frequency fluctuation (ALFF) are employed to explore spontaneous brain function in patients with aMCI. This study applied ALFF and ReHo indicators to analyze the neural mechanism of aMCI by resting-state functional magnetic resonance imaging (rs-fMRI).MethodsTwenty-six patients with aMCI were included and assigned to the aMCI group. The other 26 healthy subjects we… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

1
2
0

Year Published

2024
2024
2025
2025

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 10 publications
(3 citation statements)
references
References 37 publications
1
2
0
Order By: Relevance
“…The result proved that the left STG is a shared substrate for auditory short-term memory and speech comprehension (Leff et al, 2009). Yue et al also found alterations in the amplitude of low frequency fluctuation in the STG of aMCI patients, positively correlated with MoCA scores, proposing that abnormalities in the STG might be related to dysfunction across multiple cognitive domains, consistent with the findings of this study (Yue et al, 2023). Furthermore, ROC analysis demonstrated that the FC of the left STG contributes to distinguishing aMCI with different levels of EF.…”
Section: Discussionsupporting
confidence: 90%
See 1 more Smart Citation
“…The result proved that the left STG is a shared substrate for auditory short-term memory and speech comprehension (Leff et al, 2009). Yue et al also found alterations in the amplitude of low frequency fluctuation in the STG of aMCI patients, positively correlated with MoCA scores, proposing that abnormalities in the STG might be related to dysfunction across multiple cognitive domains, consistent with the findings of this study (Yue et al, 2023). Furthermore, ROC analysis demonstrated that the FC of the left STG contributes to distinguishing aMCI with different levels of EF.…”
Section: Discussionsupporting
confidence: 90%
“…Amnestic mild cognitive impairment (aMCI), which serves as a prodromal stage of Alzheimer's disease (AD), is considered an intermediate stage between normal aging and AD (W. Bai et al., 2022 ; Petersen et al., 2014 ). The core characteristic of aMCI is a decline in episodic memory (EM) function, closely associated with disease progression (Cova et al., 2017 ; Grande et al., 2021 ; Yue et al., 2023 ). Statistics indicate that approximately 10%–15% of aMCI patients convert to AD each year (Jessen et al., 2014 ).…”
Section: Introductionmentioning
confidence: 99%
“…This may be due to the fact that the sample size of this study was the largest of any published articles on rs-fMRI in patients with CD. The function of these brain regions is important for cognitive and emotional regulation ( Li et al, 2021b ; Yue et al, 2023 ; Zhao et al, 2023 ). Our neuroimaging findings may provide a neurophysiological substrate that may potentially explain the symptoms of psychological impairment observed in patients with CD, beyond the inflammatory stage.…”
Section: Discussionmentioning
confidence: 99%